SEIZURES IN CHILDREN WITH LOW GRADE GLIOMA - Ostwal, Piyush; Nandan, Shanbhag (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Seizures are a common presentation of pediatric brain tumors. The incidence of pediatric brain tumor (Age 0-19 years) ranges from 1.12â€“5.26 cases per 100,000 persons. Low grade gliomas are an important subgroup of pediatric brain tumors causing epilepsy. Low-grade gliomas are largely slow-growing tumors and the manifestations are dependent on age, location, tumor type, size of tumor and rate of tumor growth. Seizures have been reported in up to 38 % of children with supratentorial tumors. The tumors are identified when work up of patients for epilepsy includes electrophysiological and imaging studies. The primary treatment modality remains surgical excision. Antiepileptic medications are used for control of seizures. Subsequent histopathological diagnosis is important for prognostication. The tumors commonly associated with long-term epilepsy in various studies were ganglioglioma, dysembryoplastic neuroepithelial tumor, pilocytic astrocytoma and pilocytic xanthoastrocytoma. The outcome of surgery with regards to seizure control is generally good. Though concomitantly antiepileptic medications will be needed for most of them.Â An attempt is made in this review to summarize the epidemiology, clinical features, pathology and treatment aspects of pediatric low grade gliomas presenting with seizures.